Current pet ownership modifies the adverse association between long‐term ambient air pollution exposure and childhood asthma - Zeng, Xiao‐Wen (Clin Transl Allergy, 2021)
BACKGROUND: Recent studies suggest that household endotoxin and allergens can modify the impact of air pollutants on development of asthma; however, epidemiological evidence is limited and conflicting. OBJECTIVES: To investigate whether pet ownership modified the association between ambient air pollution and asthma in children. METHODS: We conducted a population‐based cross‐sectional study, the Seven Northeast Cities Study in China and recruited a total of 59,754 children from 94 schools during 2012–2013. Long‐term air pollutant concentrations, including airborne particulate matter with a diameter of 1 μm or less (PM(1)), PM(2.5), PM(10), and nitrogen dioxide (NO(2)) from 2009 to 2012 were estimated using a random forest model. We collected information of respiratory health in children using the Epidemiologic Standardization Project Questionnaire of the American Thoracic Society (ATS‐DLD‐78‐A). Regression models were used to evaluate associations between pet ownership and air pollution on asthma after adjusting for potential covariates. RESULTS: Exposure to increasing levels of air pollutants was associated with higher prevalence of asthma, but associations were significantly attenuated in children who owned pets. For example, compared to children without pets, those who owned pets did not have an increased risk of symptoms of asthma (odds ratio, 1.01, 95% confidence interval: 0.78, 1.30), wheeze (0.96, 95% confidence interval [CI]: 0.76, 1.21), and cough (1.01, 95% CI: 0.87, 1.18) for each 10 µg/m(3) increase in PM(1) (P (‐int) < 0.05). Similar trends were observed for other air pollutants. Dog and bird ownership decreased the associations of asthma and cough with air pollutant exposure. The main findings were consistent with a series of sensitivity analyses. CONCLUSION: Current pet ownership may reduce the adverse impact of long‐term air pollution on childhood asthma. Longitudinal studies are needed to confirm this finding which could have important implications for public health.